Frictional nanogenerators (TENGs) in medical health monitoring: A progress review - Yuanyuan Pan; Guanling Wang; Kai Wang (AIP Advances)
Triboelectric nanogenerators (TENGs), as a revolutionary energy-harvesting technology, have garnered widespread attention in the scientific community for their efficient conversion of mechanical energy into electrical energy. This article first outlines the five working modes of TENGs: vertical contact-separation mode, horizontal sliding mode, single-electrode mode, independent layer mode, and free-standing rotating mode, and elaborates on their working principles in detail. Subsequently, this article delves into the application examples of TENGs in wearable health monitoring devices, implantable medical devices, and environmental health monitoring, fully demonstrating the vast potential of TENG technology in medical health monitoring. In addition, this article analyzes the advantages of TENG technology, including its self-powered characteristics, high sensitivity, and good biocompatibility, while also pointing out the challenges that it faces, such as improving long-term stability, enhancing energy conversion efficiency, and environmental adaptability. This review aims to explore the progress of TENG technology in medical health monitoring, analyze its advantages and challenges, and look forward to future development directions. Through a systematic analysis of existing literature, this article will provide researchers and developers with in-depth insights into guiding future research and product development.